Labeling of Polysaccharides with Biotin and Fluorescent Dyes - Alexander Tuzikov; Nadezhda Shilova; Tatiana Ovchinnikova; Alexey Nokel; Olga Patova; Yuriy Knirel; Tatiana Chernova; Tatiana Gorshkova; Nicolai Bovin (Polysaccharides, 2023)
Examples of labeling polysaccharides at hydroxyl groups are described in this paper, which are especially in demand for molecules with a blocked reducing end. The protocols presented are suitable for the microscale synthesis of labeled polysaccharides that do not require a chromatography step for isolation. Examples of hydroxyl labeling include (1) direct modification with fluorescein isothiocyanate; (2) reaction with a fluorescein-dichlorotriazine derivative; (3) reaction with biotin-dichlorotriazine; (4) indirect two-step modification (given for glycosphingolipid) with glutaric anhydride followed by amidation with aminospacered BODIPY or SuCy5. The labeling of carboxyl groups of hyaluronic acid with BODIPY is also described. The staining of plant tissue sections with biotinylated polysaccharide versus being fluorescein labeled is compared.